Sport Psychology and sports in nature: integrative review - Folharini, Luisa Rodrigues (2022)
BACKGROUND: Sports in Nature involve inhospitable places, unpredictability, risks from the natural environment and various emotions. To try to understand the psychological aspects involved in these activities, the research focused on the survey of studies already carried out focusing on these sports.OBJECTIVE: Identify the articles published in Brazil, about Sport Psychology that presented Sports in Nature as a central modality.METHODS: The Integrative review method was applied, with 6 steps: 1. Identification of the theme (relationship between Psychology and Sports in Nature), choice of databases (Scielo, Lilacs), with identified descriptors; 2. Inclusion and exclusion criteria; 3. Identification of the selected studies (640 found, 12 selected); 4. Categorization of studies; 5. Analysis of the results; 6. Presentation of the review.RESULTS: In total, 640 papers were found, from which 12 articles were selected that met the inclusion and exclusion criteria. From the full reading, there was a discussion on the topics covered and the identification of gaps, new questions for investigations and the possibilities of professionals in Physical Education and Sport Psychology in the context of Sports in Nature.CONCLUSION: Several psychological aspects are involved in the field of Sports in Nature, such as choosing the sport, safe practice, taking advantage of the benefits of these sports and even training and acting as instructors. From the research included in the present study, it was possible to verify the scientific production in several themes such as mood states; motivation, adherence; flow state; concentration; self-knowledge; behaviors; self-confidence and self-efficacy, as well as it allowed to envision the Physical Education professional as a mediator of these practices in the midst of nature and as a possible promoter of a more positive life, a contrasting factor to the scarcity of scientific production in this area in the Brazilian scenario.